Copper phosphide negative pole piece for sodium ion battery and preparation method of copper phosphide negative pole piece
By using copper phosphide negative electrode material in sodium ion batteries, combining conductive agents and polymer binders to form a mesh structure, the problems of low capacity and large volume expansion of the negative electrode material of sodium ion batteries are solved, and higher specific capacity and cycling stability are achieved.
Patent Information
- Application Number
- CN202311342786.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-17
- Publication Date
- 2025-04-18
AI Technical Summary
The negative electrode material of existing sodium ion batteries has low hard carbon capacity, while the volume of traditional phosphide negative electrode material expands, affecting the cycling stability of the battery.
Copper phosphide is used as the negative electrode material, and a network structure is formed by using it in conjunction with a conductive agent and a polymer binder containing a carboxyl group and/or hydroxyl group, and the particle size of copper phosphide is controlled to be between 500 nm and 10 μm, and is uniformly dispersed in the network structure to suppress volume expansion.
It improves the specific capacity and cycle stability of sodium ion batteries, enhances the conductivity and rate performance of the battery, solves the problem of volume expansion, and is suitable for large-scale production.
Smart Images

Figure CN119852322A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion battery materials, and in particular to a copper phosphide negative electrode sheet for a sodium ion battery and a preparation method thereof. Background Art
[0002] With the increasing market demand for electrochemical energy storage devices, as well as the relative scarcity and rapid price increases of lithium ore resources, people are in urgent need of developing a new type of energy storage device. Sodium batteries have gradually entered the public's field of vision due to their low cost, but the energy density of sodium batteries is relatively low. In order to better play its advantages, it is necessary to further improve its energy density.
[0003] Negative electrode materials are an important component of sodium storage battery equipment. The amount of sodium ions that can be stored per unit mass of negative electrode materials represents the mass specific capacity of the material as an electrode material. The specific capacity of traditional hard carbon negative electrode materials is low. Currently, single phosphorus or phosphide is used as the negative electrode material of sodium ion batteries to improve the specific capacity. However, the existing negative electrode plates prepared by single phosphorus or phosphide have the problem of large volume expansion, which affects the cycle stability of the battery. Therefore, finding negative electrode materials with higher mass specific capacity and better stability has become one of the main research directions in the field of sodium battery material technology. Summary of the invention
[0004] The purpose of the present invention is to provide a copper phosphide negative electrode sheet for sodium ion batteries and a preparation method thereof, so as to solve the problems of low capacity of existing commercial negative electrode materials such as hard carbon and large volume expansion of traditional phosphide negative electrode materials.
[0005] To this end, in a first aspect, an embodiment of the present invention provides a copper phosphide negative electrode sheet for a sodium ion battery, the copper phosphide negative electrode sheet comprising: copper phosphide, a conductive agent and a binder;
[0006] Wherein, the copper phosphide is prepared by a solid phase method after uniformly mixing a phosphorus source material and a copper source material;
[0007] The binder is a polymer containing carboxyl and / or hydroxyl groups;
[0008] The mass ratio of the copper phosphide, the conductive agent and the binder is [80%-95%]: [3%-10%]: [2%-10%];
[0009] The copper ions in the copper phosphide and the polar functional groups of the polymer undergo cross-linking to form a network structure; the copper phosphide is uniformly dispersed in the network structure;
[0010] The particle size D of the copper phosphide 50 500nm-10μm.
[0011] Preferably, the phosphorus source material specifically includes: one or more of red phosphorus, black phosphorus, purple phosphorus, sodium phosphate, sodium phosphite, sodium hypophosphite, potassium phosphate, magnesium phosphate, and calcium phosphate;
[0012] The copper source material specifically includes: one or more of copper powder, copper oxide, cuprous oxide, cupric chloride, cuprous chloride, copper sulfate, and copper nitrate.
[0013] Preferably, the binder specifically includes: one or more of sodium alginate, sodium carboxymethyl cellulose, chitosan, polyacrylic acid, pectin, and xanthan gum;
[0014] The conductive agent includes one or more of acetylene black, carbon nanotubes, Ketjen black, conductive graphite, and graphene.
[0015] Preferably, the particle size D of the copper phosphide is 50 1μm.
[0016] In a second aspect, an embodiment of the present invention provides a method for preparing the copper phosphide negative electrode sheet described in the first aspect, the preparation method comprising:
[0017] Placing a phosphorus source material and a copper source material in a ball mill according to a certain proportion and performing ball milling to obtain a mixed material;
[0018] The mixed material is placed in a tubular furnace under a protective atmosphere, heated and calcined, and taken out after cooling to obtain copper phosphide;
[0019] Copper phosphide, a conductive agent, and a binder are mixed in proportion, and a solvent is added and stirred to obtain a negative electrode slurry;
[0020] The negative electrode slurry is coated on copper foil and dried in a vacuum drying oven to obtain a copper phosphide negative electrode sheet.
[0021] Preferably, the phosphorus source material includes: one or more of red phosphorus, black phosphorus, purple phosphorus, sodium phosphate, sodium phosphite, sodium hypophosphite, potassium phosphate, magnesium phosphate, and calcium phosphate;
[0022] The copper source material includes: one or more of copper powder, copper oxide, cuprous oxide, cupric chloride, cuprous chloride, copper sulfate, and copper nitrate;
[0023] The mass ratio of the phosphorus source material to the copper source material is [1:9]-[9:1].
[0024] Preferably, the binder includes: one or more of sodium alginate, sodium carboxymethyl cellulose, chitosan, polyacrylic acid, pectin, and xanthan gum;
[0025] The conductive agent includes: one or more of acetylene black, carbon nanotubes, Ketjen black, conductive graphite, and graphene;
[0026] The mass ratio of the copper phosphide, the conductive agent and the binder is [80%-95%]: [3%-10%]: [2%-10%];
[0027] The solvent is deionized water; the mass percentage of the solvent to the mass percentage of the negative electrode slurry is 10%-30%.
[0028] Preferably, the ball milling speed is 200r / min-2000r / min, and the ball milling time is 7 hours-16 hours;
[0029] The protective atmosphere is an argon atmosphere or a nitrogen atmosphere;
[0030] The heating calcination temperature is 250°C-400°C, the holding time is 3 hours-8 hours, and the heating rate is between 2°C / min-6°C / min;
[0031] The drying temperature is 60° C.-120° C., and the drying time is 6 hours-12 hours.
[0032] In a third aspect, an embodiment of the present invention provides a sodium ion battery, comprising a positive electrode plate, the copper phosphide negative electrode plate described in the first aspect, an electrolyte or a solid electrolyte, and a diaphragm.
[0033] Preferably, the sodium ion battery comprises any one of a sodium salt battery, an organic sodium ion battery, an aqueous sodium ion battery, and an all-solid-state sodium ion battery.
[0034] The embodiment of the present invention provides a copper phosphide negative electrode sheet for sodium ion battery and a preparation method thereof. First, the particle size range of the prepared copper phosphide is controlled to be D 50 Between 500nm-10μm, and then used in combination with a conductive agent and a polymer binder containing carboxyl and / or hydroxyl groups to obtain a copper phosphide negative electrode sheet; wherein, the copper ions in the copper phosphide and the polar functional groups of the polymer undergo cross-linking to form a network structure, and the interaction between the copper phosphide and the polymer is stronger, making the electrode structure more stable, and part of the copper phosphide is evenly dispersed in the network structure, so that the volume expansion of the copper phosphide can be suppressed by the network structure, further improving the structural stability of the negative electrode sheet, and maintaining the structural integrity of the negative electrode sheet during the cycle; in addition, phosphorus has a high theoretical specific capacity, and by reacting with copper-containing substances, copper phosphide with a low degree of volume expansion and a relatively high specific capacity is formed, which is used in the preparation of the negative electrode sheet, and the synergistic effect of the components in the negative electrode sheet is used to improve the conductivity and cycle performance of the battery.
[0035] The method for preparing a copper phosphide negative electrode sheet for a sodium ion battery provided in an embodiment of the present invention is simple to operate, low in cost, and applicable to large-scale production, and has practical significance for the industrial application of sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] The technical solution of the embodiment of the present invention is further described in detail below through the drawings and examples.
[0037] Figure 1 It is a flow chart of a method for preparing a copper phosphide negative electrode sheet provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0038] The present invention is further described in detail below through the accompanying drawings and specific embodiments, but it should be understood that these embodiments are only used for more detailed description and should not be understood as limiting the present invention in any form, that is, they are not intended to limit the protection scope of the present invention.
[0039] An embodiment of the present invention provides a copper phosphide negative electrode sheet for a sodium ion battery. The copper phosphide negative electrode sheet includes: copper phosphide, a conductive agent and a binder; the mass ratio of the copper phosphide, the conductive agent and the binder is [80%-95%]: [3%-10%]: [2%-10%].
[0040] Among them, the particle size D of copper phosphide 50 The copper phosphide is prepared by a solid phase method after uniformly mixing a phosphorus source material and a copper source material; the phosphorus source material specifically includes: one or more of red phosphorus, black phosphorus, purple phosphorus, sodium phosphate, sodium phosphite, sodium hypophosphite, potassium phosphate, magnesium phosphate, and calcium phosphate; the copper source material specifically includes: one or more of copper powder, copper oxide, cuprous oxide, cupric chloride, cuprous chloride, copper sulfate, and copper nitrate.
[0041] The binder is a polymer containing carboxyl and / or hydroxyl groups; the binder specifically includes: one or more of sodium alginate, sodium carboxymethyl cellulose, chitosan, polyacrylic acid, pectin, and xanthan gum;
[0042] The copper ions in the copper phosphide and the polar functional groups of the polymer undergo cross-linking to form a network structure; the copper phosphide is evenly dispersed in the network structure.
[0043] The conductive agent includes one or more of acetylene black, carbon nanotubes, Ketjen black, conductive graphite, and graphene.
[0044] The embodiment of the present invention provides a method for preparing the copper phosphide negative electrode sheet of the first aspect, such as Figure 1 As shown, the specific methods include the following:
[0045] Step 110, placing the phosphorus source material and the copper source material in a ball mill according to a certain proportion and performing ball milling to obtain a mixed material;
[0046] The phosphorus source material includes one or more of red phosphorus, black phosphorus, purple phosphorus, sodium phosphate, sodium phosphite, sodium hypophosphite, potassium phosphate, magnesium phosphate, and calcium phosphate;
[0047] The copper source material includes: one or more of copper powder, copper oxide, cuprous oxide, cupric chloride, cuprous chloride, copper sulfate, and copper nitrate;
[0048] The mass ratio of the phosphorus source material to the copper source material is [1:9]-[9:1], preferably 5:1;
[0049] The ball milling speed is 200r / min-2000r / min, and the ball milling time is 7 hours-16 hours.
[0050] Step 120, heating and calcining the mixed material in a tube furnace under a protective atmosphere, and taking it out after cooling to obtain copper phosphide;
[0051] Wherein, the protective atmosphere is an argon atmosphere or a nitrogen atmosphere;
[0052] The heating calcination temperature is 250℃-400℃, the holding time is 3 hours-8 hours, and the heating rate is between 2℃ / min-6℃ / min;
[0053] The particle size D of the copper phosphide prepared in this step is 50 The particle size D of copper phosphide is 500nm-10μm, and can be any value within this range, for example, 500nm, 600nm, 700nm, 800nm, 900nm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, etc., but is not limited to the listed values, and other values not listed within the numerical range are also applicable; the particle size D of copper phosphide 50 When it is less than 500nm, the contact points between particles will increase, increasing the resistance; the particle size of copper phosphide D 50 When it is larger than 10 μm, the compactness of the electrode structure will be reduced, which is not conducive to the transport of sodium ions. 50 The preferred particle size is 1 μm; the particle size of the copper phosphide is controlled by controlling the ball milling speed and ball milling time in step 110.
[0054] Step 130, copper phosphide, a conductive agent, and a binder are mixed in proportion, and a solvent is added and stirred to obtain a negative electrode slurry;
[0055] Wherein, the binder includes: one or more of sodium alginate, sodium carboxymethyl cellulose, chitosan, polyacrylic acid, pectin, and xanthan gum;
[0056] The conductive agent includes: one or more of acetylene black, carbon nanotubes, Ketjen black, conductive graphite, and graphene;
[0057] The mass ratio of copper phosphide, conductive agent and binder is [80%-95%]: [3%-10%]: [2%-10%];
[0058] The solvent is deionized water; the mass percentage of the solvent to the mass percentage of the negative electrode slurry is 10%-30%.
[0059] Step 140, coating the negative electrode slurry on copper foil and drying it in a vacuum drying oven to obtain a copper phosphide negative electrode sheet;
[0060] The drying temperature is 60°C-120°C, and the drying time is 6 hours-12 hours.
[0061] The copper phosphide negative electrode sheet prepared by the above-mentioned preparation method of the present invention can be assembled into a sodium ion battery together with a positive electrode sheet, an electrolyte or a solid electrolyte, and a separator. Since copper phosphide has a higher specific capacity and a smaller volume expansion than traditional negative electrode material hard carbon, it is used in the preparation of negative electrode sheets to improve the conductivity, rate performance and cycle stability of the sodium ion battery. In the process of preparing the negative electrode sheet in the embodiment of the present invention, the binder used in combination with copper phosphide is a polymer containing carboxyl and / or hydroxyl groups. The copper ions in the copper phosphide and the polar functional groups of the polymer are cross-linked to form a network structure. The interaction between the copper phosphide and the polymer is stronger, making the electrode sheet structure more stable. Part of the copper phosphide is evenly dispersed in the network structure, which can inhibit the volume expansion of copper phosphide and further maintain the integrity of the negative electrode sheet. While improving the specific capacity of the sodium ion battery, it can also improve or maintain the cycle stability of the sodium ion battery.
[0062] The above-mentioned sodium ion battery includes any one of: a sodium salt battery, an organic sodium ion battery, an aqueous sodium ion battery, and an all-solid-state sodium ion battery.
[0063] In order to better understand the technical solution provided by the present invention, the preparation process and characteristics of the copper phosphide negative electrode sheet of the present invention are respectively described below with multiple specific examples.
[0064] Example 1
[0065] This embodiment provides a preparation process and performance test of a copper phosphide negative electrode sheet, and the specific process is as follows.
[0066] (1) 1 kg of cuprous oxide powder and sodium hypophosphite powder in a mass ratio of 1:5 were placed in a ball mill for ball milling for 7 hours at a rotation speed of 750 r / min to obtain a mixed material.
[0067] (2) The mixed material was calcined in a tubular furnace at 350°C for 3 hours under a nitrogen atmosphere at a heating rate of 4°C / min. After cooling, copper phosphide with a particle size of D 50 1μm.
[0068] (3) Copper phosphide, acetylene black and binder sodium alginate were mixed in a mass ratio of 92:5:3, deionized water was added, and the mixture was stirred in a stirrer at a speed of 2000 r / min for 2 hours to obtain a negative electrode slurry, wherein the deionized water accounted for 30% of the mass of the negative electrode slurry.
[0069] (4) Coat the negative electrode slurry on copper foil and control the loading to 2 mg / cm 2 , put it into a vacuum drying oven at 80℃ and dry it for 12 hours, then take it out and cut it into discs with a diameter of 12mm using a cutting machine to obtain a copper phosphide negative electrode sheet.
[0070] The copper phosphide negative electrode sheet prepared in this embodiment was assembled into a sodium ion button cell and tested.
[0071] The specific battery assembly process is as follows: the battery is assembled in a glove box filled with high-purity argon gas, the positive electrode is a metal sodium sheet, the diaphragm is made of glass fiber, and the electrolyte is 1 mol / L NaClO 4 A solution in ethylene carbonate (EC) / diethyl carbonate (DEC) (the volume ratio of EC and DEC is 1:1).
[0072] The test process is: use a charge and discharge instrument to perform constant current charge and discharge mode testing, the discharge cut-off voltage is 0.005V, the charge cut-off voltage is 1.5V, the first cycle rate is 0.2C, and subsequent tests are performed at 2C current density.
[0073] The test data of the first cycle coulombic efficiency, initial discharge specific capacity and capacity retention rate after 100 cycles of the sodium ion button battery prepared in this embodiment are shown in Table 1.
[0074] Example 2
[0075] This embodiment provides a preparation process and performance test of a copper phosphide negative electrode sheet, and the specific process is as follows.
[0076] (1) 1 kg of copper oxide powder and red phosphorus powder in a mass ratio of 2:1 were placed in a ball mill for ball milling for 10 hours at a rotation speed of 1300 r / min to obtain a mixed material.
[0077] (2) The mixed material was calcined in a tubular furnace under a nitrogen atmosphere at 400°C for 3 hours at a heating rate of 3°C / min. After cooling, copper phosphide was obtained with a particle size of D 50 is 500nm.
[0078] (3) Copper phosphide, Ketjen black and a binder, sodium carboxymethyl cellulose, were mixed in a mass ratio of 92:5:3, deionized water was added, and the mixture was stirred in a stirrer at a speed of 2000 r / min for 2 hours to obtain a negative electrode slurry, wherein the deionized water accounted for 30% of the mass of the negative electrode slurry.
[0079] (4) Coat the negative electrode slurry on copper foil and control the loading to 2 mg / cm 2 , put it into a 90℃ vacuum drying oven and dry it for 10 hours, then take it out and cut it into 12mm diameter discs with a cutting machine to obtain the copper phosphide negative electrode sheet.
[0080] The copper phosphide negative electrode sheet prepared in this embodiment was assembled into a sodium ion button cell and tested.
[0081] The specific battery assembly process is as follows: the battery is assembled in a glove box filled with high-purity argon gas, the positive electrode is a metal sodium sheet, the diaphragm is made of glass fiber, and the electrolyte is 1 mol / L NaClO 4 A solution in ethylene carbonate (EC) / diethyl carbonate (DEC) (the volume ratio of EC and DEC is 1:1).
[0082] The test process is: use a charge and discharge instrument to perform constant current charge and discharge mode testing, the discharge cut-off voltage is 0.005V, the charge cut-off voltage is 1.5V, the first cycle rate is 0.2C, and subsequent tests are performed at 2C current density.
[0083] The test data of the first cycle coulombic efficiency, initial discharge specific capacity and capacity retention rate after 100 cycles of the sodium ion button battery prepared in this embodiment are shown in Table 1.
[0084] Example 3
[0085] This embodiment provides a preparation process and performance test of a copper phosphide negative electrode sheet, and the specific process is as follows.
[0086] (1) 1 kg of copper chloride powder and black phosphorus powder in a mass ratio of 3:2 were placed in a ball mill for ball milling for 10 hours at a rotation speed of 1000 r / min to obtain a mixed material.
[0087] (2) The mixed material was calcined in a tubular furnace at 400°C for 5 hours under a nitrogen atmosphere at a heating rate of 2°C / min. After cooling, copper phosphide was obtained with a particle size of D 50 It is 800nm.
[0088] (3) Copper phosphide, carbon nanotubes and binder polyacrylic acid were mixed in a mass ratio of 92:5:3, deionized water was added, and the mixture was stirred in a stirrer at a speed of 1500 r / min for 2 hours to obtain a negative electrode slurry, wherein the deionized water accounted for 30% of the mass of the negative electrode slurry.
[0089] (4) Coat the negative electrode slurry on copper foil and control the loading to 2 mg / cm 2 , put it into a 90℃ vacuum drying oven and dry it for 10 hours, then take it out and cut it into 12mm diameter discs with a cutting machine to obtain the copper phosphide negative electrode sheet.
[0090] The copper phosphide negative electrode sheet prepared in this embodiment was assembled into a sodium ion button cell and tested.
[0091] The specific battery assembly process is as follows: the battery is assembled in a glove box filled with high-purity argon gas, the positive electrode is a metal sodium sheet, the diaphragm is made of glass fiber, and the electrolyte is 1 mol / L NaClO 4 A solution in ethylene carbonate (EC) / diethyl carbonate (DEC) (the volume ratio of EC and DEC is 1:1).
[0092] The test process is: use a charge and discharge instrument to perform constant current charge and discharge mode testing, the discharge cut-off voltage is 0.005V, the charge cut-off voltage is 1.5V, the first cycle rate is 0.2C, and subsequent tests are performed at 2C current density.
[0093] The test data of the first cycle coulombic efficiency, initial discharge specific capacity and capacity retention rate after 100 cycles of the sodium ion button battery prepared in this embodiment are shown in Table 1.
[0094] Example 4
[0095] This embodiment provides a preparation process and performance test of a copper phosphide negative electrode sheet, and the specific process is as follows.
[0096] (1) 1 kg of cuprous chloride powder and sodium phosphate powder in a mass ratio of 3:1 were placed in a ball mill for ball milling for 10 hours at a rotation speed of 800 r / min to obtain a mixed material.
[0097] (2) The mixed material was calcined in a tubular furnace under a nitrogen atmosphere at 300°C for 5 hours at a heating rate of 2°C / min. After cooling, copper phosphide was obtained with a particle size of D 50 1μm.
[0098] (3) Copper phosphide, graphene and binder chitosan were mixed in a mass ratio of 92:5:3, deionized water was added, and the mixture was stirred in a stirrer at a speed of 2000 r / min for 2 hours to obtain a negative electrode slurry, wherein the deionized water accounted for 30% of the mass of the negative electrode slurry.
[0099] (4) Coat the negative electrode slurry on copper foil and control the loading to 2 mg / cm 2 , put it into a 90℃ vacuum drying oven and dry it for 10 hours, then take it out and cut it into 12mm diameter discs with a cutting machine to obtain the copper phosphide negative electrode sheet.
[0100] The copper phosphide negative electrode sheet prepared in this embodiment was assembled into a sodium ion button cell and tested.
[0101] The specific battery assembly process is as follows: the battery is assembled in a glove box filled with high-purity argon gas, the positive electrode is a metal sodium sheet, the diaphragm is made of glass fiber, and the electrolyte is 1 mol / L NaClO 4 A solution in ethylene carbonate (EC) / diethyl carbonate (DEC) (the volume ratio of EC and DEC is 1:1).
[0102] The test process is: use a charge and discharge instrument to perform constant current charge and discharge mode testing, the discharge cut-off voltage is 0.005V, the charge cut-off voltage is 1.5V, the first cycle rate is 0.2C, and subsequent tests are performed at 2C current density.
[0103] The test data of the first cycle coulombic efficiency, initial discharge specific capacity and capacity retention rate after 100 cycles of the sodium ion button battery prepared in this embodiment are shown in Table 1.
[0104] Example 5
[0105] This embodiment provides a preparation process and performance test of a copper phosphide negative electrode sheet, and the specific process is as follows.
[0106] (1) 1 kg of copper sulfate powder and calcium phosphate powder in a mass ratio of 6:1 were placed in a ball mill for ball milling for 10 hours at a rotation speed of 600 r / min to obtain a mixed material.
[0107] (2) The mixed material was calcined in a tubular furnace at 350°C for 6 hours under a nitrogen atmosphere at a heating rate of 3°C / min. After cooling, copper phosphide was obtained with a particle size of D 50 5μm.
[0108] (3) Copper phosphide, conductive graphite and binder carboxymethyl chitosan were mixed in a mass ratio of 92:5:3, deionized water was added, and the mixture was stirred in a stirrer at a speed of 1500 r / min for 2 hours to obtain a negative electrode slurry, wherein the deionized water accounted for 30% of the mass of the negative electrode slurry.
[0109] (4) Coat the negative electrode slurry on copper foil and control the loading to 2 mg / cm 2 , put it into a 90℃ vacuum drying oven and dry it for 10 hours, then take it out and cut it into 12mm diameter discs with a cutting machine to obtain the copper phosphide negative electrode sheet.
[0110] The copper phosphide negative electrode sheet prepared in this embodiment was assembled into a sodium ion button cell and tested.
[0111] The specific battery assembly process is as follows: the battery is assembled in a glove box filled with high-purity argon gas, the positive electrode is a metal sodium sheet, the diaphragm is made of glass fiber, and the electrolyte is 1 mol / L NaClO 4 A solution in ethylene carbonate (EC) / diethyl carbonate (DEC) (the volume ratio of EC and DEC is 1:1).
[0112] The test process is: use a charge and discharge instrument to perform constant current charge and discharge mode testing, the discharge cut-off voltage is 0.005V, the charge cut-off voltage is 1.5V, the first cycle rate is 0.2C, and subsequent tests are performed at 2C current density.
[0113] The test data of the first cycle coulombic efficiency, initial discharge specific capacity and capacity retention rate after 100 cycles of the sodium ion button battery prepared in this embodiment are shown in Table 1.
[0114] Example 6
[0115] This embodiment provides a preparation process and performance test of a copper phosphide negative electrode sheet, and the specific process is as follows.
[0116] (1) 1 kg of copper nitrate powder and magnesium phosphate powder in a mass ratio of 3:4 were placed in a ball mill for ball milling for 10 hours at a rotation speed of 1400 r / min to obtain a mixed material.
[0117] (2) The mixed material was calcined in a tubular furnace at 350°C for 6 hours under a nitrogen atmosphere at a heating rate of 5°C / min. After cooling, copper phosphide was obtained with a particle size of D 50 is 500nm.
[0118] (3) Copper phosphide, Ketjen black and a binder, sodium carboxymethyl cellulose, were mixed in a mass ratio of 92:5:3, deionized water was added, and the mixture was stirred in a stirrer at a speed of 1500 r / min for 2 hours to obtain a negative electrode slurry, wherein the deionized water accounted for 30% of the mass of the negative electrode slurry.
[0119] (4) Coat the negative electrode slurry on copper foil and control the loading to 2 mg / cm 2 , put it into a 90℃ vacuum drying oven and dry it for 10 hours, then take it out and cut it into 12mm diameter discs with a cutting machine to obtain the copper phosphide negative electrode sheet.
[0120] The copper phosphide negative electrode sheet prepared in this embodiment was assembled into a sodium ion button cell and tested.
[0121] The specific battery assembly process is as follows: the battery is assembled in a glove box filled with high-purity argon gas, the positive electrode is a metal sodium sheet, the diaphragm is made of glass fiber, and the electrolyte is 1 mol / L NaClO 4A solution in ethylene carbonate (EC) / diethyl carbonate (DEC) (the volume ratio of EC and DEC is 1:1).
[0122] The test process is: use a charge and discharge instrument to perform constant current charge and discharge mode testing, the discharge cut-off voltage is 0.005V, the charge cut-off voltage is 1.5V, the first cycle rate is 0.2C, and subsequent tests are performed at 2C current density.
[0123] The test data of the first cycle coulombic efficiency, initial discharge specific capacity and capacity retention rate after 100 cycles of the sodium ion button battery prepared in this embodiment are shown in Table 1.
[0124] Example 7
[0125] This embodiment provides a preparation process and performance test of a copper phosphide negative electrode sheet, and the specific process is as follows.
[0126] (1) 1 kg of cuprous oxide powder and potassium phosphate powder in a mass ratio of 9:1 were placed in a ball mill for ball milling for 13 hours at a rotation speed of 900 r / min to obtain a mixed material.
[0127] (2) The mixed material was calcined in a tubular furnace at 350°C for 6 hours under a nitrogen atmosphere at a heating rate of 5°C / min. After cooling, copper phosphide was obtained with a particle size of D 50 It is 900nm.
[0128] (3) Copper phosphide, acetylene black and a binder, sodium carboxymethyl cellulose, were mixed in a mass ratio of 92:5:3, deionized water was added, and the mixture was stirred in a stirrer at a speed of 1500 r / min for 2 hours to obtain a negative electrode slurry, wherein the deionized water accounted for 30% of the mass of the negative electrode slurry.
[0129] (4) Coat the negative electrode slurry on copper foil and control the loading to 2 mg / cm 2 , put it into a 90℃ vacuum drying oven and dry it for 8 hours, then take it out and cut it into discs with a diameter of 12mm using a cutting machine to obtain a copper phosphide negative electrode sheet.
[0130] The copper phosphide negative electrode sheet prepared in this embodiment was assembled into a sodium ion button cell and tested.
[0131] The specific battery assembly process is as follows: the battery is assembled in a glove box filled with high-purity argon gas, the positive electrode is a metal sodium sheet, the diaphragm is made of glass fiber, and the electrolyte is 1 mol / L NaClO 4 A solution in ethylene carbonate (EC) / diethyl carbonate (DEC) (the volume ratio of EC and DEC is 1:1).
[0132] The test process is: use a charge and discharge instrument to perform constant current charge and discharge mode testing, the discharge cut-off voltage is 0.005V, the charge cut-off voltage is 1.5V, the first cycle rate is 0.2C, and subsequent tests are performed at 2C current density.
[0133] The test data of the first cycle coulombic efficiency, initial discharge specific capacity and capacity retention rate after 100 cycles of the sodium ion button battery prepared in this embodiment are shown in Table 1.
[0134] In order to better illustrate the effects of the embodiments of the present invention, comparative examples 1-2 are compared with the above embodiments.
[0135] Comparative Example 1
[0136] This comparative example provides a preparation process and performance test of a negative electrode sheet, wherein the preparation process of copper phosphide is the same as that of Example 1, and the difference from Example 1 is that the binder used in preparing the negative electrode sheet is polyvinylidene fluoride. The specific preparation process of the negative electrode sheet is: copper phosphide powder, acetylene black and binder polyvinylidene fluoride are mixed in a solvent in a mass ratio of 92:5:3, stirred in a stirrer at a speed of 2000r / min for 2 hours, and the slurry is coated on an aluminum foil, and the load is controlled to be 2mg / cm 2 , put it into a vacuum drying oven at 80℃ and dry it for 12 hours, then take it out and cut it into pole pieces with a diameter of 12mm using a cutting machine to obtain the negative pole piece.
[0137] The assembly and measurement methods of the button cell of this comparative example are the same as those of Example 1. The test data of the first cycle coulombic efficiency, initial discharge specific capacity and capacity retention rate after 100 cycles of the sodium ion button cell prepared in this comparative example are shown in Table 1.
[0138] Comparative Example 2
[0139] This comparative example provides a preparation process and performance test of a hard carbon negative electrode sheet, and the specific process is as follows.
[0140] Preparation of negative electrode sheet: Mix hard carbon negative electrode material, Ketjen black and binder polyvinylidene fluoride in a solvent at a mass ratio of 92:5:3, stir in a mixer at a speed of 2000r / min for 2 hours, and apply the slurry on aluminum foil with a controlled loading of 2mg / cm 2 , put it into a vacuum drying oven at 80℃ and dry it for 12 hours, then take it out and cut it into pole pieces with a diameter of 12mm using a cutting machine to obtain the negative pole piece.
[0141] The assembly and measurement methods of the button cell of this comparative example are the same as those of Example 1. The test data of the first cycle coulombic efficiency, initial discharge specific capacity and capacity retention rate after 100 cycles of the sodium ion button cell prepared in this comparative example are shown in Table 1.
[0142] Table 1 is a summary of the test data of the first cycle coulombic efficiency, initial discharge specific capacity and capacity retention rate after 100 cycles of the sodium ion button batteries prepared in Examples 1-7 and Comparative Examples 1-2.
[0143]
[0144] Table 1
[0145] By comparing the data in Table 1, it can be seen that the first cycle coulombic efficiency, initial discharge specific capacity and capacity retention rate after 100 cycles of the sodium ion button batteries of Examples 1-7 are much higher than those of Comparative Example 1. The first cycle coulombic efficiency and initial discharge specific capacity of the sodium ion button batteries of Examples 1-7 are much higher than those of Comparative Example 2. This is because the sodium ion button batteries of Examples 1-7 use the copper phosphide negative electrode sheet of the present invention. On the one hand, phosphorus itself has a relatively high theoretical specific capacity. Although the specific capacity of the formed compound copper phosphide is slightly lower than that of phosphorus alone, the volume expansion of copper phosphide is relatively small. Using it to prepare the negative electrode sheet can improve the conductivity and cycle stability of the battery. On the other hand, in the process of preparing the negative electrode sheet, the embodiments of the present invention are combined with phosphorus. The binder used in combination with copper phosphide is a polymer containing carboxyl and / or hydroxyl groups. The copper ions in the copper phosphide and the polar functional groups of the polymer undergo cross-linking to form a network structure. The interaction between the copper phosphide and the polymer is stronger, which makes the electrode structure more stable, and part of the copper phosphide is evenly dispersed in the network structure, thereby inhibiting the volume expansion of the copper phosphide and further improving the structural stability of the negative electrode. For example, by comparing the test data of Example 1 and Comparative Example 1, it can be seen that when the copper phosphide negative electrode material is used in combination with the sodium alginate binder containing carboxyl and hydroxyl groups, the electrochemical performance of the battery is improved. This is because the binder polyvinylidene fluoride used in Comparative Example 1 has a weaker interaction force and is difficult to withstand the volume expansion of the copper phosphide negative electrode material.
[0146] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A copper phosphide negative electrode sheet for a sodium ion battery, characterized in that: The copper phosphide negative electrode plate comprises: copper phosphide, a conductive agent and a binder; Wherein, the copper phosphide is prepared by a solid phase method after uniformly mixing a phosphorus source material and a copper source material; The binder is a polymer containing carboxyl and / or hydroxyl groups; The mass ratio of the copper phosphide, the conductive agent and the binder is [80%-95%]: [3%-10%]: [2%-10%]; The copper ions in the copper phosphide and the polar functional groups of the polymer undergo cross-linking to form a network structure; the copper phosphide is uniformly dispersed in the network structure; The particle size D of the copper phosphide 50 500nm-10μm.
2. The copper phosphide negative electrode sheet according to claim 1, characterized in that: The phosphorus source material specifically includes: one or more of red phosphorus, black phosphorus, purple phosphorus, sodium phosphate, sodium phosphite, sodium hypophosphite, potassium phosphate, magnesium phosphate, and calcium phosphate; The copper source material specifically includes: one or more of copper powder, copper oxide, cuprous oxide, cupric chloride, cuprous chloride, copper sulfate, and copper nitrate.
3. The copper phosphide negative electrode sheet according to claim 1, characterized in that: The binder specifically includes: one or more of sodium alginate, sodium carboxymethyl cellulose, chitosan, polyacrylic acid, pectin, and xanthan gum; The conductive agent includes one or more of acetylene black, carbon nanotubes, Ketjen black, conductive graphite, and graphene.
4. The copper phosphide negative electrode sheet according to claim 1, characterized in that: The particle size D of the copper phosphide 50 1μm.
5. A method for preparing the copper phosphide negative electrode sheet according to any one of claims 1 to 4, characterized in that: The preparation method comprises: Placing a phosphorus source material and a copper source material in a ball mill according to a certain proportion and performing ball milling to obtain a mixed material; The mixed material is placed in a tubular furnace under a protective atmosphere, heated and calcined, and taken out after cooling to obtain copper phosphide; Copper phosphide, a conductive agent, and a binder are mixed in proportion, and a solvent is added and stirred to obtain a negative electrode slurry; The negative electrode slurry is coated on copper foil and dried in a vacuum drying oven to obtain a copper phosphide negative electrode sheet.
6. The preparation method according to claim 5, characterized in that: The phosphorus source material includes: one or more of red phosphorus, black phosphorus, purple phosphorus, sodium phosphate, sodium phosphite, sodium hypophosphite, potassium phosphate, magnesium phosphate, and calcium phosphate; The copper source material includes: one or more of copper powder, copper oxide, cuprous oxide, cupric chloride, cuprous chloride, copper sulfate, and copper nitrate; The mass ratio of the phosphorus source material to the copper source material is [1:9]-[9:1].
7. The preparation method according to claim 5, characterized in that: The binder includes: one or more of sodium alginate, sodium carboxymethyl cellulose, chitosan, polyacrylic acid, pectin, and xanthan gum; The conductive agent includes: one or more of acetylene black, carbon nanotubes, Ketjen black, conductive graphite, and graphene; The mass ratio of the copper phosphide, the conductive agent and the binder is [80%-95%]: [3%-10%]: [2%-10%]; The solvent is deionized water; the mass percentage of the solvent to the mass percentage of the negative electrode slurry is 10%-30%.
8. The preparation method according to claim 5, characterized in that: The ball milling speed is 200r / min-2000r / min, and the ball milling time is 7 hours-16 hours; The protective atmosphere is an argon atmosphere or a nitrogen atmosphere; The heating calcination temperature is 250°C-400°C, the holding time is 3 hours-8 hours, and the heating rate is between 2°C / min-6°C / min; The drying temperature is 60° C.-120° C., and the drying time is 6 hours-12 hours.
9. A sodium ion battery, characterized in that: The sodium ion battery comprises a positive electrode plate, a copper phosphide negative electrode plate as described in any one of claims 1 to 4, an electrolyte or a solid electrolyte, and a diaphragm.
10. The sodium ion battery according to claim 9, characterized in that: The sodium ion battery includes any one of a sodium salt battery, an organic sodium ion battery, an aqueous sodium ion battery, and an all-solid-state sodium ion battery.
Citation Information
Patent Citations
Use of novel compounds as active negative electrode material in sodium-ion battery
CN105659414A
Sodium ion negative electrode material, preparation method and sodium ion battery
CN114373910A
Integrated vending machine system with multiple sales modules
KR102310220B1